Attenuated Postprandial GLP-1 Response in Parkinson’s Disease - Manfready, Richard A.; Engen, Phillip A.; Verhagen Metman, Leo; Sanzo, Gabriella; Goetz, Christopher G.; Hall, Deborah A.; Forsyth, Christopher B.; Raeisi, Shohreh; Voigt, Robin M.; Keshavarzian, Ali (Frontiers in Neuroscience, 2021)
The incretin hormone glucagon-like peptide 1 (GLP-1) has neuroprotective effects in animal models of Parkinson’s disease (PD), and GLP-1 receptor agonists are associated with clinical improvements in human PD patients. GLP-1 is produced and secreted by intestinal L-cells in response to consumption of a meal. Specifically, intestinal microbiota produce short chain fatty acids (SCFA) which, in turn, promote secretion of GLP-1 into the systemic circulation, from which it can enter the brain. Our group and others have reported that PD patients have an altered intestinal microbial community that produces less short chain fatty acids compared to age-matched controls. In this report, we demonstrate that PD patients have diminished GLP-1 secretion in response to a meal compared to their household controls. Peak post-prandial GLP-1 levels did not correlate with PD disease severity, motor function, or disease duration. These data provide the scientific rationale for future studies designed to elucidate the role of GLP-1 in the pathogenesis of PD and test the potential utility of GLP-1-directed therapies.